Once Upon a Virus: AIDS Legends and Vernacular Risk Perception - Goldstein, Diane E (Utah State University, University Libraries, 2004)
Once Upon a Virus explores how contemporary, or ""urban,"" legends are indicators of culturally complex attitudes toward health and illness. Tracing the rich tradition of AIDS legends in relation to current scholarship on belief, Diane Goldstein shows how such stories not only articulate widespread perceptions of risk, health care, and health policy, they also influence official and scientific approaches to the disease and its management. Notions that appear in narratives of who gets AIDS, how and why, are indicators of broad issues involving health beliefs, concerns, and needs.